Дуплексне сканування екстракраніальних відділів хребтових артерій у хворих на гіпотиреоз - Зубкова, С. Т.; Михайленко, О. Ю. (Clinical Endocrinology and Endocrine Surgery, 2012)
Duplex scanning of the vertebral arteries was performed in patients with overt hypothyroidism associated with arterial hypertension or without it. The development of the vascular wall remodeling, manifestated in their deformation, increase in diameter was revealed in the majority of patients. A change in the vascular structure is accompanied by hemodynamic disorders: the blood flow acquires hypertonic, atherosclerotic or vasospastic character, accompanied by a decrease in systolic blood flow velocity. The observed changes were revealed more often in patients with hypothyroidism, combined with arterial hypertension.